Synergistic enhancement of ternary poly(3,4-ethylenedioxythiophene)/graphene oxide/manganese oxide composite as a symmetrical electrode for supercapacitors - Azman, Nur Hawa Nabilah; Lim, Hong Ngee; Mamat @ Mat Nazir, Md Shuhazlly; Sulaiman, Yusran (MDPI, 2018)
A novel facile preparation of poly(3,4-ethylenedioxythiophene)/graphene oxide/manganese oxide (PEDOT/GO/MnO2) ternary composite as an electrode material for a supercapacitor was evaluated. The ternary composite was sandwiched together and separated by filter paper soaked in 1 M KCl in order to investigate the supercapacitive properties. The ternary composite exhibits a higher specific capacitance (239.4 F/g) compared to PEDOT/GO (73.3 F/g) at 25 mV/s. The incorporation of MnO2 which act as a spacer in the PEDOT/GO helps to improve the supercapacitive performance by maximizing the utilization of electrode materials by the electrolyte ions. The PEDOT/GO/MnO2 ternary composite displays a specific energy and specific power of 7.9 Wh/kg and 489.0 W/kg, respectively. The cycling stability test revealed that the ternary composite is able to achieve 95% capacitance retention even after 1000 cycles due to the synergistic effect between the PEDOT, GO, and MnO2 that helps to enhance the performance of the ternary composite for supercapacitor application.